Turning Task-Adjusted Temporary Newcomers into Permanent Employees: An Identity Perspective - Montani, Francesco; Bullini Orlandi, Ludovico; Dufour, Lucas; Manca, Claudia (Journal of Management, 2026)
While most of the socialization literature has focused on factors that allow newcomers to adjust to their new job tasks successfully, less attention has been given to examining whether temporary newcomers’ task adjustment influences the likelihood of receiving a permanent position. Drawing on the identity perspective and the socialization literature, this study proposes and tests a new framework that examines the probability of task-adjusted newcomers receiving a permanent job offer contingent on two conditions: a) there is a low level of peer divestiture socialization, which enables the task-adjusted newcomer to achieve higher levels of task performance, and b) the newcomer displays low rule-following behavior, which allows the high-performing newcomer to be cognitively trusted by the supervisor. Consistent with our predictions, the results of a four-wave, multisource study featuring 194 newcomer-supervisor dyads revealed that newcomer task adjustment was positively related to the newcomer receiving a permanent job offer by way of newcomer task performance and supervisor trust in newcomers but only when peer divestiture socialization and newcomer rule-following behavior were low. We discuss the theoretical and managerial implications of these findings.